Epigenetic gene regulation in plants and its potential applications in crop improvement - Zhang, Heng; Zhu, Jian-Kang (Nature reviews. Molecular cell biology, 2025)
DNA methylation, also known as 5-methylcytosine, is an epigenetic modification that has crucial functions in plant growth, development and adaptation. The cellular DNA methylation level is tightly regulated by the combined action of DNA methyltransferases and demethylases. Protein complexes involved in the targeting and interpretation of DNA methylation have been identified, revealing intriguing roles of methyl-DNA binding proteins and molecular chaperones. Structural studies and in vitro reconstituted enzymatic systems have provided mechanistic insights into RNA-directed DNA methylation, the main pathway catalysing de novo methylation in plants. A better understanding of the regulatory mechanisms will enable locus-specific manipulation of the DNA methylation status. CRISPR–dCas9-based epigenome editing tools are being developed for this goal. Given that DNA methylation patterns can be stably transmitted through meiosis, and that large phenotypic variations can be contributed by epimutations, epigenome editing holds great promise in crop breeding by creating additional phenotypic variability on the same genetic material. This Review outlines progress in understanding the mechanisms of DNA methylation regulation in plants. Studies in various plants have revealed novel and diverse biological functions of DNA methylation that might assist in developing epigenome editing approaches suitable for crop breeding.